1998
DOI: 10.3109/13682829809179445
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Botulinum Toxin Treatment of Spasmodic Dysphonia: A Review of 22 Studies

Abstract: This meta-analysis focuses on the treatment effects of the use of botulinum toxin in laryngeal dystonia. The vocal symptoms are characterized by spasms of the laryngeal muscles thus the use of the term spasmodic dysphonia (SD). The objective of the intervention, i.e. botulinum toxin treatment, is to reduce or eliminate the vocal spasms and thus improve the acoustic regularity of the voice. The purpose of the present study was to assess the efficacy of botulinum toxin in the treatment of SD by engaging in a 'be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 0 publications
0
27
0
3
Order By: Relevance
“…[4] Botulinum toxin injections generally improve the voice for a period of three to four months, after which the voice symptoms gradually return. [1,5,6,7] Behavioral therapy and voice therapy are another form of treatment that may work in mild cases or can be used with pharmacotherapy as adjunct for increasing the duration of effect.…”
Section: Spasmodic Dysphonia Is Classified Into Three Types A) Adductmentioning
confidence: 99%
“…[4] Botulinum toxin injections generally improve the voice for a period of three to four months, after which the voice symptoms gradually return. [1,5,6,7] Behavioral therapy and voice therapy are another form of treatment that may work in mild cases or can be used with pharmacotherapy as adjunct for increasing the duration of effect.…”
Section: Spasmodic Dysphonia Is Classified Into Three Types A) Adductmentioning
confidence: 99%
“…For the patient and for the physician, BT therapy of spasmodic dysphonia represents a highly satisfying indication [ 66 ]. Practically all patients benefi t from BT therapy and the degree of improvement is astonishing.…”
Section: Pharyngolaryngeal Dystoniamentioning
confidence: 99%
“…For spasmodic dysphonia (SD), there is data from several clinical studies and meta-analyses [Wong et al 1995;Brin et al 1998;Whurr et al 1998;Finnegan et al 1999;Boutsen et al 1998;Watts et al 2006Watts et al , 2008Blitzer, 2010]. One double-blind, placebo-controlled study examined the effects of BoNT-A versus saline in 13 adductor SD patients and revealed significant effects of BoNT-A on voice quality, perceived voice improvement and acoustic measurements [Troung et al 1991].…”
Section: Spasmodic Dysphoniamentioning
confidence: 99%